Gender inequality and the empowerment of women in rural Viet Nam - Carol Newman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper examines gender inequality and female empowerment in rural Viet Nam. Using an extensive panel dataset on 2,181 households, we examine how the welfare of women living in rural areas has evolved during a period of dramatic rural transformation, 2008 - 14. We find that while the economic situation of women has improved, significant gender disparities remain, particularly for female-headed households. Women continue to bear a greater burden of responsibility for income-generating activities within households. Evidence suggests, however, that women are more empowered in 2014 than in 2008 and that this is related to higher levels of household welfare more generally.
Keywords: D13; O12; J16; 330; gender disparity; female empowerment; Vietnam